The Smart Police and its Role in Detecting the Commission of a Crimes in the Emirati Society: - Abdul Hamid, Emad El Din Mohamed Kamel (Dirasat: Human and Social Sciences, 2023)
Objectives: This study compares Smart Police and Traditional Police, examining their job roles, working mechanisms, and devices. It assesses the role of Smart Police and its applications in crime prevention in the UAE and other leading countries. The research explores UAE legislation governing Smart Police, verifying the authenticity of their evidence in criminal cases. Methods: The study employed an inductive approach to delve into the nature of Smart Police work and legislation, gaining a comprehensive understanding of its roles, mechanisms, applications, and devices in combating crimes. Additionally, a comparative analytical approach was used to analyze relevant legislation and compare international experiences, highlighting Smart Police's role in crime prevention. Results: The study reveals that there is a difference between Smart Police and Traditional Police in terms of their job roles, working mechanisms, and the used devices. The experiences of America, Singapore and the UAE in the field of Smart Police have proven their effective role in combating crimes and limiting their commission. The UAE has set out numerous special penal legislation that establishes and supports the mechanisms and functions of the Smart Police System by providing for the authenticity of Smart Police evidence and its criminal evidence output, although some of these legislation needs to be amended. Conclusions: The study recommends amending UAE Federal Law No. (5) of 2017 on remote communication technology in criminal procedures. It also advocates for establishing a centralized federal body for smart police and a dedicated electronic judiciary for cybercrime cases.